Parallèles phonétiques romano-slaves - Bednarczuk, Leszek (Neophilologica, 2010)
Recent research on the phonetic development of proto-Slavic leads one to the conclusion that the phonetic structure of the word, which was part of the Balto-Slavic heritage, underwent significant restructuring resulting from a string of interlaced processes such as (1) loss of vowel length distinctions, (2) monophthongization of diphthongs, (3) emerging of nasalized vowels, (4) loss of glides, (5) palatal assimilation before /j/ and front vowels, (6) a tendency to open syllables and its ramifications (simplification of consonant clusters and disappearance of consonants in word-final position. The array of changes, as observed in proto-Slavic, have also been attested in the evolution of the Romance group. Since the Romance changes took place earlier and are well documented, they can be used to determine the order of and the rationale behind the parallel processes in proto-Slavic.